Análise espacial e quimiométrica da distribuição de espécies metálicas em solos alagáveis e não alagáveis da Bacia do Médio Rio Negro, Amazônia - Mirela Cristina de Oliveira Cordovil; André Gustavo Ribeiro Mendonça; Wander Gustavo Botero; Ademir dos Santos; Julio Cesar Rocha; Kaline de Mello; Rogério Hartung Toppa; Luciana Camargo de Oliveira (Química Nova, 2014)
This study used chemometric tools and a Geographic Information System (GIS) to determine the influence of organic matter and anthropogenic activity on the distribution of metal species between two major communities of the Middle Negro River Basin-AM. Higher concentrations of metal species were determined in flooded regions. The chemometric analysis showed the affinity of organic matter for potentially toxic metals, indicating its selectivity. GIS spatial analysis has shown that proximity to urban areas is a variable that is likely to influence the pattern of concentration of organic matter, and consequently the distribution of metal species between flooded and non-flooded areas.